Rhythmic Auditory Stimulation In Gait Rehabilitation For Children And Youth Following Acquired Brain Injury. (2nd June 2019) - Kelly, Gemma; Pool, Jonathan
Abstract : Background/Aims: Relearning to walk is an important goal for many children and young people after acquired brain injury. Rhythmic auditory stimulation uses rhythm to support gait retraining. Its efficacy has been shown for adults with acquired brain injury and children and young people with cerebral palsy. No studies exist for children and young people with acquired brain injury. The aim of this pilot study was to investigate whether the addition of rhythmic auditory stimulation to standard physiotherapy improves children and young people's gait speed and quality after severe acquired brain injury. Methods: Four children and young people (aged 10–13 years) with severe acquired brain injury accessing residential rehabilitation were recruited to a multiple baseline single case experimental design study, AB design. During baseline (A) phase children and young people accessed standard rehabilitation (10 physiotherapy sessions per week). In the intervention (B) phase, 2 out of the 10 standard physiotherapy sessions were replaced with rhythmic auditory stimulation. Length of baseline was randomised and intervention phases were 4 weeks. The 10 m walk test and Edinburgh Visual Gait Scale were completed pre and post sessions biweekly. Data analysis including visual analysis of level, slope and trend of the data will be presented with the results of a test of statistical significance. Results: Data collection will finish in December 2018. Early results indicate that the quality of walking improved more during the intervention phase than the baseline phase for at least one of the participants, and rhythmic auditory stimulation was equal to normal physiotherapy in the other participants. Statistical testing is required. Conclusions: Early results indicate that rhythmic auditory stimulation is at least as effective as normal physio in improving the walking quality of children and young people with acquired brain injury, but this needs to be confirmed. Recommendations for clinical practice and future studies can be made based on the findings and experience of this study.